Perfil multidimensional de personas que han realizado intento de suicidio - Núñez Gómez , Nicolas Arturo (2022)
The purpose of this study is to establish a multidimensional profile of people who have attempted to commit suicide. 116 cases of people with reported suicide attempts in emergency rooms and educational institutions in the department of Huila were studied. This was a descriptive study, with a semi-structured interview, personality test, depression inventory, alcohol evaluation, ideation and suicide attempt evaluations. The multidimensional profile consisted of adolescents from rural areas, city-dwelling adults, also taking into account housewives with stable relationships, single, divorced and unemployed persons. The relationship between low neuroticism and high psychoticism could help to explain ‘unexpected’ suicide attempts without previous symptoms. The structure and dynamics of dysfunctional families are strongly associated with suicide attempts.